2016
DOI: 10.1186/s40557-016-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and inflammatory markers in male workers aged 20–39 in a display manufacturing company

Abstract: BackgroundThis study aimed to determine the association between shift work and inflammatory markers, which are independent risk factors of cardiovascular diseases, in male manual workers at a display manufacturing company.MethodsThis study was conducted between June 1 and July 31, 2015 on 244 male manual workers aged 20–39 years old at a display manufacturing company and investigated age, marital status, education level, alcohol consumption habit, smoking habit, regular exercise habit, sleep duration, sleep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 49 publications
8
28
0
Order By: Relevance
“…In the present analysis, we found no association between recent night shift work and CRP levels. Other epidemiologic studies have observed higher CRP levels among rotating night shift workers and other night shift workers, consistent with our findings of associations between years of rotating night shifts and CRP levels . A new finding from our study was a stronger association between night shift work and CRP among nurses who had the highest CRP levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present analysis, we found no association between recent night shift work and CRP levels. Other epidemiologic studies have observed higher CRP levels among rotating night shift workers and other night shift workers, consistent with our findings of associations between years of rotating night shifts and CRP levels . A new finding from our study was a stronger association between night shift work and CRP among nurses who had the highest CRP levels.…”
Section: Discussionsupporting
confidence: 92%
“…In a small trial, individuals allocated 4 hours per night in bed for 10 nights had a significant increase in C‐reactive protein (CRP) levels, a finding not observed among those allowed 8 hours per night in bed . These findings were later confirmed in another similar trial and in studies of night workers . Other studies show that sleep restriction results in glucose intolerance, elevations in blood pressure, higher levels of inflammatory cytokines, and coronary artery calcification …”
Section: Introductionmentioning
confidence: 88%
“…[19][20][21] This association persisted even when participants with chronic disease were excluded, and after adjustment for multiple confounding factors, supporting that shiftwork might independently contribute to systemic inflammation. Previous studies have also reported higher systemic inflammation in shiftworkers [31,32], and this might be one mechanism through which shiftwork could contribute to the risk of cardiometabolic disease.…”
Section: Discussionmentioning
confidence: 79%
“…Circadian rhythms, the body’s autonomous internal clock based on intricate transcriptional and translational feedback loops, anticipate and allow organisms to adapt to environmental changes by controlling a wide array of physiological and metabolic processes ( 64 ). Lifestyles that disrupt the inherent biological clock, such as shift work, have been associated with increased systemic levels of inflammatory markers ( 65 , 66 ) as well as increased incidence of cardiovascular disease ( 67 ), metabolic disorders ( 68 , 69 ), and cancer ( 70 , 71 ). Interestingly, trafficking and migration of immune cells, including T cells, is also regulated by circadian rhythms ( 72 ) although the exact impact of these fluctuations on T cell function remains to be fully elucidated ( 73 , 74 ).…”
Section: The Inflammatory Microenvironmentmentioning
confidence: 99%